2011
DOI: 10.1509/jmkg.75.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Referral Programs and Customer Value

Abstract: Referral programs have become a popular way to acquire customers. Yet there is no evidence to date that customers acquired through such programs are more valuable than other customers. The authors address this gap and investigate the extent to which referred customers are more profitable and more loyal. Tracking approximately 10,000 customers of a leading German bank for almost three years, the authors find that referred customers (1) have a higher contribution margin, though this difference erodes over time;(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
159
1
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 28 publications
5
159
1
15
Order By: Relevance
“…Villanueva et al [37] show that customers who joined the firm as a result of WOM recommendations of social connections add almost twice as much long-term value to the firm than customers who did not join as a result of WOM. The same was found by Schmitt et al [33]. They concluded that the difference in customer lifetime value between referred (attracted as a result of WOM recommendations) and non-referred customers is at least 16%.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Villanueva et al [37] show that customers who joined the firm as a result of WOM recommendations of social connections add almost twice as much long-term value to the firm than customers who did not join as a result of WOM. The same was found by Schmitt et al [33]. They concluded that the difference in customer lifetime value between referred (attracted as a result of WOM recommendations) and non-referred customers is at least 16%.…”
Section: Introductionsupporting
confidence: 77%
“…This is driven by the growing acceptance of the fact that people are highly influenced by information received from others [17] and that word-of-mouth (WOM) is the most influential source of information to a customer [21]. Empirical research confirmed that consumers rely heavily on the advice of others in their personal network when making purchase decisions [19,36,32,20,33] and that positive WOM has a positive effect on business outcomes, i.e. sales [31,3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Verhoef and Donkers (2005) find that acquisition through the Internet leads to higher retention rates than acquisition through direct mail or direct-response commercials. A second set of papers addresses the impact of customer referral (Chan, Wu, and Xie 2011;Schmitt, Skiera, and Van den Bulte 2011). Villanueva, Yoo, and Hanssens (2008), for instance, show that customers acquired through word-of-mouth referral have longer lifetimes.…”
mentioning
confidence: 99%
“…Engaging options proposed in Section 5 show similar characteristics as referral programs studied in [29]. By helping the Cloud provider to better utilize its virtualized hardware, the energy consumption accounted to the users accounts can be reduced.…”
Section: Related Workmentioning
confidence: 94%
“…By helping the Cloud provider to better utilize its virtualized hardware, the energy consumption accounted to the users accounts can be reduced. Research shows that such programs can achieve up to 16% better results [29]. Referrals are often more personal than normal advertisements or SLAs and, therefore, show a high impact on user behavior as showed in [30].…”
Section: Related Workmentioning
confidence: 98%